2021
DOI: 10.1002/bab.2115
|View full text |Cite
|
Sign up to set email alerts
|

High production of d‐psicose from d‐fructose by immobilized whole recombinant Bacillus subtilis cells expressing d‐psicose 3‐epimerase from Agrobacterium tumefaciens

Abstract: D-Psicose 3-epimerase (DPEase) can catalyze the isomerization of D-fructose to be rare sugar D-psicose, which has wide application prospects in the food and medical fields. In this study, the DPEase gene from Agrobacterium tumefaciens was constructed into plasmid pMA5, and was successfully expressed in the host Bacillus subtilis WB600 (B. subtilis). After optimization of the fermentation conditions, whole recombinant B. subtilis WB600/pMA5-At-DEPase(O) cells produced D-psicose from D-fructose with a conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Commercially available allulose is manufactured from D-fructose because it is an epimer of D-fructose (Jia et al, 2021). It is synthesised from D-fructose via an enzymatic process (Wang et al, 2022). A recent investigation suggested that D-psicose content in processed foods was as high as 130.6 mg/100 g of fresh weight.…”
Section: Emerging Sources Of Healthier Sweetenersmentioning
confidence: 99%
“…Commercially available allulose is manufactured from D-fructose because it is an epimer of D-fructose (Jia et al, 2021). It is synthesised from D-fructose via an enzymatic process (Wang et al, 2022). A recent investigation suggested that D-psicose content in processed foods was as high as 130.6 mg/100 g of fresh weight.…”
Section: Emerging Sources Of Healthier Sweetenersmentioning
confidence: 99%
“…Wang et al immobilized B. subtilis whole-cells that expressed recombinant DPEase onto a gel bead biocatalyst using Ca-alginate. The immobilized biocatalyst showed a higher thermal/pH stability and storability with a d -allulose productivity of 32.83 ± 2.56 g/L, while the free cells produced only about 10.44 ± 0.07 g/L [ 138 ].…”
Section: Enzymatic Biotransformation Of D -Allulosementioning
confidence: 99%